Predicting Temperature of Corrosion Scale Formation Carbon Steel in Oil and Gas Environment - Y.P., Asmara; Jeya Gopi, Raman; A.G.E, Sutjipto (INTI International University, 2019)
Formation of scales on the metal surface during corrosion process in oil and gas environment is one of the important parameter in predicting corrosion rate. The scales are formed on metal surface at specific temperature. Quality of the scales depend on service temperature, concentration of carbon-dioxide (CO2) and acetic acid (HAc) as main elements in oil and gas environments. This research aims to determine scale formation temperature on of carbon steel under different concentration of CO2 and HAc using mathematics formulas. The corrosion rate for carbon steel was calculated using linear resistance polarization (LPR) test methods. Specimens were placed in a beaker contained 3.5% NaCl connected to a CO2 cylinder for CO2 gas bubbling. The corrosion tests were conducted at room temperature, 60 oC and 80oC in several concentration of CO2 and HAc. A statistical analysis with response surface methodology (RSM) was used to process the model to predict corrosion scale temperature using second-degree model mathematics formulas. An attempt will also be made to verify the results using data literatures. As results, the predictions show in acceptable ranges (70% – 80 %) as compared to experimental data from literatures.